In situ bubble template-assisted synthesis of phosphonate-functionalized Rh nanodendrites and their catalytic application. Issue 21 (18th May 2017) - Zhu, Jing-Yi; Li, Fu-Min; Yao, Lin; Han, Cong-Cong; Li, Shu-Ni; Zeng, Jing-Hui; Jiang, Jia-Xing; Lee, Jong-Min; Chen, Yu
Abstract : The phosphonate-functionalized Rh nanodendrites with hippocampus tail-like branches exhibited excellent catalytic activity and durability for the o -phenylenediamine oxidation reaction. Abstract : The controllable synthesis of branched noble metal nanostructures has attracted significant attention as it provides excellent catalytic activity and durability to these metal nanostructures. In the present study, a facile and effective complexation–reduction strategy was developed for synthesizing Rh nanodendrites with hippocampus tail-like branches (Rh-NDHTs) using N2 H4 ·H2 O as a reductant and multiphosphonate molecule with small molecular weight as a complexant and functional agent. During the synthesis, the coordination interaction between multiphosphonate and RhCl3 as well as the hydrazine decomposition reaction (H2 NNH2 = N2 + 2H2 ) catalyzed by the freshly formed Rh nanocrystals play important roles in the generation of Rh-NDHTs. Moreover, phosphonate functionalization of Rh-NDHTs was simultaneously achieved during the course of the synthesis, originating from the strong adsorption of multiphosphonate on the Rh surface. When used as a heterogeneous catalyst for the o -phenylenediamine oxidation reaction, the phosphonate-functionalized Rh-NDHTs exhibited enhanced catalytic efficiency and durability as compared to the commercially available Rh nanocrystals, attributing to their extraordinary morphological and interfacial properties.